Instilling Financial Literacy in the Foster Children of the An-Nuriyyah Bekasi Orphanage - Riwayati, Hedwigis Esti; Ridarmelli, Ridarmelli; Retnaningsih, Inung Wijayanti; Jasman, Jasman; Haron, Rosmawati; Othman, Akmal Aini (Dinasti Publisher, 2025)
Financial literacy is an important skill to master from an early age. Children who have an understanding of finance will be better prepared to face future economic challenges, manage money wisely, and make better financial decisions. This article is the result of a collaboration between Perbanas Institute and UiTM Johor Malaysia at the An-Nuriyyah Orphanage Bekasi, West Java, Indonesia. The form of activities is in the form of lectures, demonstrations, video screenings and games that aim to provide an understanding of financial literacy from an early age and the benefits obtained if you understand financial literacy. In forming healthy financial habits for the community from an early age, the participation of the government, schools and academics is needed.